TRADISI PENGANUGERAHAN IJAZAH DALAM SISTEM PENDIDIKAN ISLAM: KAJIAN SELAYANG PANDANG - Mesut Idriz; Idha Nurhamidah (Universitas Islam Sultan Agung, 2019)
The current article aimed at presenting an overview of types, requirements and procedures of certification in Islam education for the students who have passed the examination in order for countries outside United Arab Emirates. Core materials on the subject were compiled from various resources to guarantee the validity of the information. It turned out that there were a number of concepts of certification pertinent to etymology and practices. One distinctive issue of certification was that, in Islam education, certification was attached to the authority of professor or sheikh, not the institution, and the government has no right whatsoever with respect to certification. This, in fact, differentiates certification in Islam World from that practiced in the West.Keywords: Certificate, Certification, Etymological Concept, Islam Education System